Carbon dynamics in no-till soil due to the use of industrial organic waste and mineral fertilizer (Revista Ciência Agronômica, 2015)
The use of organic waste from industrial processes in agriculture is a strategy not only for improving soil propertiesbut also for promoting the utilization of recycled nutrients by market crops and for reducing environmental impact. The aim ofthis study was to evaluate the effects of using organic waste from pork and poultry slaughterhouses (OWS) applied alone or incombination with mineral fertilizer (MF) on the dynamics of soil organic matter (SOM) compartments. The experimental designadopted was that of completely randomized blocks with six treatments and three replicates. The treatments consisted of a generalcontrol (T1) without the addition of MF and OWS, the application of MF alone at 100% of the recommended fertilizer levelsfor the crops (T2),the application of OWS alone at a fixed dose of 2 Mg ha-1 (T3), and the following three combinations of MFand OWS: 75% MF + 25% OWS (T4); 50% MF + 50% OWS (T5); and 25% MF + 75% OWS (T6). The application of OWSpromoted increase in the labile fractions extracted by potassium permanganate (C-OXP) and hot water (C-HW) compared withusing MF alone. Using OWS in the combination of 50% MF + 50% OWS increased the content and stock of total organic carbon(TOC) in the 0-20 cm layer and of particulate organic C (POC) and C-OXP in the 0-5 cm layer.